STUDI PENGARUH WAKTU PENGENDAPAN DAN KONSENTRASI AWAL PARTIKEL PADAT LIMBAH DARI OUTLET FLOKULATOR TERHADAP EFISIENSI PENGENDAPAN LIMBAH PADA SISTEM UTILITAS PUSRI-III - Sri Haryati (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2010)
Sludge from flocculator outlet of PUSRI-III settles along the channel and generates a problem in wastewater treatment. Aims of this research were to obtain sedimentation characteristics and variables which influenced sedimentation efficiency and to minimize slurry flow into the biological pond. This research was conducted using vertical sedimentation steel column of 10 inch diameter and 4.50 m long. A 0.50 inch valve was installed as sampling tool along the pipe in every 500 mm distant. Settling efficiency was measured at retention time range of 10-50 minutes using initial concentrations of solid particles of 400, 420, 440, 460, and 480 mg/L. Results of this study showed that settling efficiency could reach 60%-80% in retention time range of 20-40 minutes. Sedimentation rate of solid particles was not significantly influenced by the variation of initial concentration of solid particles. Results from this research can be used as a reference for sedimentation column design at flocculator outlet.